Sarcopenia Is Associated with Changes in Circulating Markers of Antioxidant/Oxidant Balance and Innate Immune Response - Francesco Bellanti; Aurelio Lo Buglio; Stefano Quiete; Michał Dobrakowski; Aleksandra Kasperczyk; Sławomir Kasperczyk; Gianluigi Vendemiale (MDPI AG, 2023)
(1) Background: The involvement of redox balance alterations and innate immunity is suggested to play a key role in the pathogenesis of sarcopenia. This investigation aimed to define and relate modifications in circulating markers of redox homeostasis and the innate immune response in human sarcopenia. (2) Methods: A total of 32 subjects aged >65 years old and affected by sarcopenia according to the second "European Working Group on sarcopenia in older people" guidelines were compared with 40 non-sarcopenic age-matched controls. To assess systemic redox homeostasis, reduced (GSH) and oxidized (GSSG) blood glutathione and plasma malondialdehyde (MDA)- and 4-hydroxy-2,3-nonenal (HNE)-protein adducts were measured. Immune cells and circulating interleukins were determined to compare the innate immune response between both groups. (3) Results: Impaired redox balance in sarcopenic patients, characterized by a high blood GSSG/GSH ratio and plasma MDA/HNE-protein adducts, was sustained by reduced antioxidants in peripheral blood mononuclear cells. Furthermore, sarcopenic patients showed higher neutrophil-to-lymphocyte ratios and interleukin (IL)-4, IL-6, IL-10, and tumor necrosis factor (TNF) with respect to non-sarcopenic patients. Linear regression analysis resulted in a strong association between redox balance and immune response markers in the sarcopenic group. (4) Conclusions: These results support the interplay between redox homeostasis alteration and disruption of the innate immune response in the pathogenesis of sarcopenia.